The role of central venous oxygen saturation, blood lactate, and central venous-to-arterial carbon dioxide partial pressure difference as a goal and prognosis of sepsis treatment - Borwon Wittayachamnankul (2018)
© 2016 Elsevier Inc. Objective The current practice in treatment of severe sepsis and septic shock is to ensure adequate oxygenation and perfusion in patients, along with prompt administration of antibiotics, within 6 hours from diagnosis, which is considered the “golden hour” for the patients. One of the goals of treatment is to restore normal tissue perfusion. With this goal in mind, some parameters have been used to determine the success of treatment and mortality rate; however, none has been proven to be the best predictor of mortality rate in sepsis patients. Despite growing evidence regarding the prognostic indicators for mortality in sepsis patients, inconsistent reports exist. Study selection This review comprehensively summarizes the reports regarding the frequently used parameters in sepsis including central venous oxygen saturation, blood lactate, and central venous-to-arterial carbon dioxide partial pressure difference, as prognostic indicators for clinical outcomes in sepsis patients. Moreover, consistent findings and inconsistent reports for their pathophysiology and the potential mechanisms for their use as well as their limitations in sepsis patients are presented and discussed. Finally, a schematic strategy for potential management and benefits in sepsis patients is proposed based upon these current available data. Conclusion There is currently no ideal biomarker that can indicate prognosis, predict progression of the disease, and guide treatment in sepsis. Further studies are needed to be carried out to identify the ideal biomarker that has all the desired properties.